Diabetes and Risk Factors in Teachers at Ica National University, Peru - Rafael Prado Prado; Yessika Madelaine Abarca Arias (Revista Finlay)
Background: diabetes mellitus is considered a worldwide public health problem. Approximately the 65 % of patients die from cardiovascular complications. Sedentary lifestyles, unhealthy eating habits, and obesity are main risk factors. Objective: to determine glucose levels and risk factors such as obesity and eating habits, in a group of teachers from the San Luis Gonzaga National University of Ica, Peru. Method: a cross-sectional and correlational descriptive study was carried out in 278 teachers from the San Luis Gonzaga National University of Ica from both sex between 40 and 70 years of age. Anthropometric data for height and weight were taken from each one; the postprandial glucose test was carried out and a questionnaire of predominant types of diet was applied to them. Data were analyzed by applying Pearson's non-parametric Chi-square statistic using contingency tables, adjusted to the 95 % confidence level. The results are shown in tables and graphs. Result: the 6 % prevalence of diabetes mellitus and the 4 % of teachers with glucose intolerance were observed, as well as the 39.2 % overweight, the 19 % obese and around the 63 % predominantly following a diet rich in carbohydrates and fats. Conclusions: there was correspondence with the diagnosis of diabetes mellitus, most of the teachers in the study were men, the group with more than 60 years of age in a condition of obesity predominated, most of the teachers follow a diet enriched in carbohydrates.